Partners' leisure time truly together upon retirement - Elena Stancanelli; Arthur Van Soest (IZA Journal of Labor Policy, 2016)
Externalities in leisure are considered an important reason for partners' joint retirement. This study quantifies the extent to which partners actually spend more leisure time "together" at retirement. Exploiting legal retirement age in France, we identify the effect of retirement on partners' hours of leisure, distinguishing leisure hours spent together or not. We find that the separate leisure demand of the husband increases dramatically upon his retirement, by about 3 h per day. The wife's retirement significantly increases both her separate leisure time and the couple's joint leisure time. Because the wife is typically the last to retire, her retirement often coincides with partners' joint retirement. Our findings confirm that leisure complementarities in retirement are significant though perhaps not very large quantitatively.
Keywords: C26; C31; J26; J22; 330; Regression discontinuity; Retirement; Leisure